Pengaruh Digital Service Quality, Kompetensi Pegawai, dan Budaya Pelayanan terhadap Kepuasan Masyarakat pada Mall Pelayanan Publik DPMPTSP Kabupaten Brebes - Jaenal Untung; Hendri Sucipto; Slamet Bambang Riono; Dumadi Dumadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims: 1) To determine and analyze the influence of Digital Service Quality on public satisfaction 2) To determine and analyze the influence of Employee Competence on public satisfaction 3) To determine and analyze the influence of Service Culture on public satisfaction 4) To determine and analyze the influence of Digital Service Quality, Employee Competence, and Service Culture simultaneously on public satisfaction. The type of research used in this study is a quantitative approach, this study has a population of 7076 with a sample of 99 respondents. Based on the analysis and discussion, it can be concluded that H1: Digital Service Quality has a positive and significant effect on Public Satisfaction at the DPMPTSP Public Service Mall in Brebes Regency with a t-count of 2.257 > 1.984 and significant, H2: Employee Competence has no effect and is not significant on Public Satisfaction at the DPMPTSP Public Service Mall in Brebes Regency with a t-count of 0.569 < 1.984 and a significant value of 0.571 > 0.05, H3: Service Culture has a positive and significant effect on Public Satisfaction at the DPMPTSP Public Service Mall in Brebes Regency with a t-count of 3.391 > 1.984 and significant, H4: Digital Service Quality, Employee Competence, and Service Culture simultaneously have a positive and significant effect on Public Satisfaction with an F-count of > F-table (8.350 > 2.696) and a significant value of 0.000 < 0.05. The coefficient of determination (Adjusted R Square) is 0.612, meaning that the variables Digital Service Quality, Employee Competence, and Service Culture collectively influence customer satisfaction by 61.2%.